(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT This article focuses on the role of literary translation in the development and enrichment of national literature. Literary translation establishes complex mutual relations between nations. It can replace and strengthen original genres (for instance during the creation of national literature) and also influence fields where the national literary output is not yet sufficient. Moreover, literary translation can allow for the development of national literature and its literary language. This paper sheds light on the role of literary translation in elevating national literature; deepening and refining the artistic, aesthetic and literary ideas and tastes of readers; and laying the foundations for the advancement and modernization of national literature.